Technology and technical means for the implementation of reproduction methods for soil fertility - Y. P. Lobachevskiy; N. V. Aldoshin (Сельскохозяйственные машины и технологии, 2024)
Soil fertility is determined by the presence of humus as the main part of organic matter. The extended reproduction of soil fertility is ensured by the introduction of organic and mineral fertilizers, the cultivation of sidereal crops and the decomposition of plant residues. (Research purpose) The research purpose is developing the technologies and means of mechanization for extended reproduction of fertility. (Materials and methods) For the joint application of liquid organic fertilizers and the cultivation of siderates, a unit has been developed that implements a hose technology for transporting liquid organic fertilizers. Fertilizers are fed through pressure hose lines to the working parts deep into the soil layer. The combined unit consists of a tractor K-744 Kirovets and an adapter for deep tillage with liquid fertilizers, as well as a seeder for small-seeded crops. To level the surface of the field after the passage of the unit and the sealing of the sown seeds of the sideral culture, the unit is equipped with a tooth roller. (Results and discussion) Formulas for determining the critical processing depth are given, the power calculation of the unit is performed. The design of the tillage tool allows to install flat-cutting working parts with a grip of 0.80 meters and slits with a grip of 0.45 meters. Tests of the combined unit were carried out. The depth of tillage was 36±1 centimeters, the seeding rate of the sideral crop (oilseed radish) was 25 kilograms per hectare, the operating speed range of the unit was from 0.4 to 0.8 meters per second. (Conclusions) The uniformity of the subsurface distribution of organic fertilizers was 90-95 percent. The specific energy intensity of the technological process of the combined unit based on the K-744 tractor for intra-soil fertilization is 40-65 kilowatt hours per hectare (excluding the capacity for pumping fertilizers). Energy consumption depends on the depth of cultivation and resistivity of the soil. The proposed method allows preventing water and wind erosion of the soil, improving its agronomically valuable properties. Reducing the pesticide load on the soil and its microflora contributes to the transition to a model of sustainable agroecosystems, improving and improving crop quality. The proposed technology provides extended reproduction of soil fertility.